Improving phosphorus availability to rice through silicon management in paddy soils: A review of the role of silicate-solubilizing bacteria - Etesami, Hassan; Schaller, Jörg (Rhizosphere, 2023)
Rice needs a lot of phosphorus (P) to grow, but much of the P fertilizers applied to paddy soils becomes unavailable to the plants. Silicon (Si) amendments can increase P availability to rice. Si is widely available in soils as insoluble silicates, but only the soluble form, monosilicic acid, can be absorbed by plants. Water-soluble Si fertilizers are effective but expensive. Using silicate-solubilizing bacteria (SSB) can help solubilize Si and improve P availability by a cheaper way. This paper reviews Si's role in improving P availability to rice, focusing on SSB's capacity to increase Si availability in soils. This knowledge can help reduce chemical P fertilizer use, P accumulation in paddy soils, and environmental risks from non-point source pollution.